1996
DOI: 10.1093/glycob/6.2.147
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structural characterization of fucosylated gangliosides with linear poly-N-acetyllactosaminyl chains from human granulocytes

Abstract: The isolation and structural characterization of fucosylated neolacto-series gangliosides with linear poly-N-acetyllactosaminyl chains from normal human granulocytes is described. Gangliosides were purified by consecutive use of anion exchange HPLC on Fractogel TMAE-650(S), adsorption and reversed phase HPLC on Nucleosil 50-7 and Nucleosil 7C18 columns, respectively. TLC immunostaining with carbohydrate specific monoclonal antibodies, fast atom bombardment-mass spectrometry (FAB-MS) of the permethylated deriva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…In prior studies, we demonstrated that polar lipids extracted from human neutrophils that were more than 98% pure supported E-selectin-but not P-selectin-mediated cell adhesion. 33 In this and prior studies, 42,56,57 GSLs from primary human leukocytes were found to include monosialylated poly-LacNAc glycosphingolipids with 5 or more LacNAc repeats and 2 or more fucose residues. Together, these data indicate that human neutrophils express monosialylated fucosylated poly-LacNAc GSLs (myeloglycans) with E-selectin-binding capacity.…”
Section: Discussionmentioning
confidence: 61%
“…In prior studies, we demonstrated that polar lipids extracted from human neutrophils that were more than 98% pure supported E-selectin-but not P-selectin-mediated cell adhesion. 33 In this and prior studies, 42,56,57 GSLs from primary human leukocytes were found to include monosialylated poly-LacNAc glycosphingolipids with 5 or more LacNAc repeats and 2 or more fucose residues. Together, these data indicate that human neutrophils express monosialylated fucosylated poly-LacNAc GSLs (myeloglycans) with E-selectin-binding capacity.…”
Section: Discussionmentioning
confidence: 61%
“…TLC immunostainings were done as described in several previous publications ( 62,63,70,72 ). In short, Stx1a-, Stx2a-, or Stx2e-containing supernatants (see Stx1a, Stx2a, Stx2e, anti-Stx, anti-GSL, and secondary antibodies above) were employed using the "microscale method" ( 39,77 ). The anti-Stx1 and anti-Stx2 antibodies were used in 1:1,000 dilutions, respectively, and primary anti-Gb3Cer and anti-Gb4Cer antibodies, as well as secondary alkaline phosphatase-conjugated antibodies, were applied in 1:2,000 dilutions each.…”
Section: Tlc Overlay Assay Of Gslsmentioning
confidence: 99%
“…Resulting 50 AL volumes were sprinkled on silica-fixed chromatograms of reference gangliosides (see Reference Gangliosides). This ''microscale method'' (because only microliter volumes of primary anti-GSL antibodies containing sera are applied in the first step of the overlay assay to strips of 1.5 Â 10 cm of size) has been described previously by Mü thing et al (25). Binding of serum antibodies was detected with secondary alkaline phosphatase -labeled anti-human IgG plus IgM antibodies.…”
Section: Tlc Overlay Assaymentioning
confidence: 99%